Oralité et écriture dans les chroniques dynastiques d’Afrique de l’Ouest - Jean Boulègue (Afriques)
West African dynastic chronicles, whether as written texts or oral traditions, are built according to the reigns, which give their internal division, while the king is at the heart of the account. Islamization did not introduce into them the Hegirian era or the lunar year. These chronicles are based on the solar year, with its seasonal rhythm, and a chronological system based on the end of the timeline, that is the enthronement of the reigning king. Thus kingship is the ruling principle of these chronicles and the choice of the mode of transmission (orality or writing) does not deny it: it does not depend on the knowledge of writing but on social and political power struggles and the choices of the ruling power.